Ushul Al-Fiqh Dan Kontribusinya (Konsep Ta’wil dan Relevansinya Dengan Pembaharuan Hukum Islam) - Syarial Dedi (Institut Agama Islam Negeri Curup, 2017)
The ta’wil is a method of istinbath al-ahkam from texts (nash). In principle ushuliyyin agreed to say the use of ta’wil, if it’s meets the existing requirements, this ta’wilis called by the trem ta’wil maqbul, that is ta’wil wich not far from the meaning of zhahir, so that with simpleintructionscan be understood. But if the ta’wil is based only foundation to impulses and unfulfilled conditions,the trasnforming of meaning of lafazh wich away from, can’t be known by a dalil of simple proposition. So this ta’wil like this is rejeced or termed is ta’wil ghair al-maqbul. But in determining of dalil of ta’wil (argumantation support), the are differencesof opinion among ushuliyyin, thus are raising the trem ta’wil baid. overall, method of ta’wil is still considered relevant to the reform of Islamic law.